Analysis Of The Impact Of Hexagonal Fraud Element On Fraud Deterrence - Sahara Novatania Yasmine; Koenta Adji Koerniawan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This research aims to identify the components of the fraud hexagon that have an impact on fraud deterrence implemented at Sentra Wyata Guna Bandung, thereby strengthening the governance and policies in place to minimize the occurrence of fraud. Data was collected through the distribution of questionnaires to 82 employees of Sentra Wyata Guna Bandung. Statements in the questionnaire were measured using a Likert scale. Respondent data were processed using descriptive statistical analysis to explain respondent characteristics, principal component analysis to reduce data dimensions, and multiple linear regression to determine the influence of each component of the fraud hexagon. The research results show that simultaneously, all components of the fraud hexagon have an influence on fraud deterrence at Sentra Wyata Guna Bandung. Partially, the rationalization and opportunity variables have a positive and significant influence, the ego variable has a positive but not significant influence, and the pressure, capability, and collusion variables have a negative but not significant influence. This research focuses on examining the application of fraud deterrence using the fraud hexagon in the social sector. Keywords: Fraud Deterrence, Fraud Hexagon, Pressure, Rationalization, Opportunity, Ego, Capability, Collusion.